Screening of rice varieties based on remodeling of root architecture linked to enhanced phosphorus transporters and ethylene signaling for better phosphorous acquisition under limiting conditions - Zulfiqar, Alveena; Azhar, Beenish Jehan; Zeb, Aroosa; Zeenat, Asyia; Aman, Sitwat; Heckerthorn, Scott A; Shakeel, Samina N (Penerbit Universiti Kebangsaan Malaysia, 2021)
Root architectural modifications in response to altered nutrient level can be used as selection marker for better adapted rice varieties. In this study, we screened six local rice varieties commonly grown in Pakistan, using their unique root architecture and several molecular markers to identify best adapted local variety under phosphorus limiting conditions. Our data showed that rice variety with significant changes in its three-dimensional root architecture system (RSA) and enhanced expression of phosphorus transporters (OsPT2, OsPT4 and OsPT6) is the best variety to handle stress as compared to other varieties. Along with development of screening strategy/method, our data provided evidence that phosphorus starvation leads to upregulation of stress hormone ethylene, which regulates root elongation and root hair development therefore facilitating root architecture modification. We then further checked, how to mitigate or enhance phosphorus starvation responses by application of hormones exogenously, our results showed that ethylene application/ treatment enhances phosphorus starvation responses, whereas cytokinin on the other hand reverses deficiency effects which implicates hormonal cross talk is key to modulate P-deficiency responses in rice. This study provides an easy and quick method of analysis of root architecture as physiological marker for rice screening and improve crop yield by selecting best adapted variety for P deficient soils. In future, detail study for understanding phytohormone mediated transcriptomic changes in response to nutrient deficiency and in correlation with physiological response will help to select better adapted varieties that will eventually result in increase of rice yield.